Innovation crisis in the pharmaceutical industry? A survey - Ute Laermann-Nguyen; Martin Backfisch (SN Business & Economics, 2021)
In the literature, it is widely discussed whether the pharmaceutical industry is going through an innovation crisis. Unfortunately, no comprehensive review exists to date that outlines the main empirical findings. In this paper, we provide an extensive survey on what is currently known about the crisis and its reasons. The empirical evidence shows that project success rates decreased over time, while attrition rates, development times, and the costs per new drug increased. The reasons for these developments are quite complex. The crisis seems to have largely technological causes. The enormous scientific progress in biotechnology and related disciplines has increased the opportunities to treat diseases, but the firms have difficulties transforming these advances into new and effective medicines. More basic research is necessary and the links between science and industry should be strengthened. Some measures have recently been taken to better adapt the approval process to current developments. However, the persistently high number of consolidations in the industry seems to have largely detrimental effects.
Keywords: L65; O31; O32; O38; 330; Innovation; R&D; Pharmaceutical industry; Drug development